Demand for Energy Goods in South Kalimantan: The Application of The Censored QUAIDS Model - Ahmadi Murjani (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
The energy subsidy reform in Indonesia is still being implemented amidst many obstacles. The policy that is taken by the government certainly needs many inputs to produce a well-planned energy subsidy reform policy. One of the inputs is the elasticity of demand for the selected energy goods. Income and price elasticity of demand are two common numbers utilized in the policy simulation. With a long timeline of the energy subsidy reform episodes, the values of such elasticities are needed to be recalculated to accommodate the dynamics of the policy. This paper aims to estimate the income and price elasticity of demand for some energy goods in Indonesia such as electricity, gasoline, diesel oil, kerosene, and LPG. After employing the censored QUAIDS model implemented in the South Kalimantan province of Indonesia, this paper arrived at conclusion. First, among all selected energy goods, gasoline, diesel oil, and kerosene are classified as luxury goods whereas electricity and LPG are necessity goods. Second, only kerosene is found price elastic among other energy goods.